Determination of the levels of heavy metals in water, pastures and meat tissues of Pedi goats across two rivers in Limpopo Province, South Africa - Manamela, Makwena Precious (My University, 2021)
The study was carried out to determine the concentration levels of mercury (Hg), lead (Pb), cadmium (Cd), chromium (Cr), nickel (Ni) and zinc (Zn) in water, soil, witbuffels grass and meat of goats reared along the river banks of Middle Olifants (Mogalatsana village) and Mogalakwena (Papegaai village) rivers. The samples were collected from the river water, soils along the river banks, grass grown along the river banks and male Pedi goats reared in Mogalatsana and Papegaai villages. The samples were analysed for the selected heavy metals with an inductively coupled plasma mass spectroscopy (ICP-MS). Data was analysed as in a complete randomised design. The results of selected heavy metals in water of both rivers ranged from 0.00 mg/litre of water (Ni and Cr) to 0.04 mg/litre of water (Hg). The concentration levels of selected heavy metals in water were similar (P>0.05) for Middle Olifants and Mogalakwena rivers. The concentration levels of selected heavy metals in the soils along the banks of Middle Olifants and Mogalakwena rivers ranged from 0.00 mg/kg DM soil (Hg and Cd) to 63.70 mg/kg DM soil (Cr). There were similar (P>0.05) concentration levels of selected heavy metals in the soils along the banks of Middle Olifants and Mogalakwena rivers. Heavy metal concentration levels in the witbuffels grass grown along the banks of Middle Olifants and Mogalakwena rivers ranged from 0.00 mg/kg DM of grass (Hg and Cd) to 5.05 mg/kg DM of grass (Zn). Similar (P>0.05) concentrations of selected heavy metals were observed in witbuffels grass grown along the banks of Middle Olifants and Mogalakwena rivers. However, the concentration levels of Zn, Pb and Cd in water from both sites were above internationally maximum permissible levels, indicating that the water from these rivers was not safe for drinking by humans and animals. The concentration levels of Ni and Pb in soils from both sites were above internationally recommended maximum permissible limits. Similarly, chromium concentration levels in witbuffels grass from both sites were above the recommended maximum permissible limits for livestock, indicating that the grass was not safe for consumption by livestock. It is recommended that further studies be conducted to ascertain these findings. Blood, liver, kidney and meat samples of yearling male Pedi goats grazing along the banks of Middle Olifants river (Mogalatsana village) had similar (P>0.05) Cr, Cd, Hg, Ni and Pb concentration levels, respectively. However, goat liver samples had higher (P<0.05) Zn concentrations than meat, kidney and blood samples. Samples of goat v meat contained higher (P<0.05) Zn concentrations than those of kidneys and blood. Similarly, goat kidney samples contained more (P<0.05) Zn than blood samples. Blood, liver, kidney and meat samples of Pedi goats grazing along the banks of Mogalakwena river (Papegaai village) contained similar (P>0.05) concentration levels of Cr, Cd, Hg, Ni and Pb, respectively. However, goat meat samples contained higher (P<0.05) Zn concentrations than liver, kidney and blood samples. Samples of goat liver contained higher (P<0.05) Zn concentration levels than kidney and blood samples. Similarly, goat kidney samples contained more (P<0.05) Zn than blood samples. Meat, blood, liver and kidney samples of male Pedi goats raised in Mogalatsana and Papegaai villages had similar (P>0.05) chromium, cadmium, mercury, nickel and lead concentrations, respectively. However, liver and kidney samples of goats from Mogalatsana village had higher (P<0.05) zinc levels than those from Papegaai village. Blood and meat samples of goats from Papegaai village had higher (P<0.05) zinc levels than those from Mogalatsana village. The concentration levels of Zn, Ni, Pb, Cr and Cd in the blood, liver, kidney and meat samples of male Pedi goats reared along the banks of Middle Olifants and Mogalakwena rivers were within the maximum permissible levels for human consumption. Mercury concentration levels in liver, kidney and meat samples of the goats were within the maximum permissible levels for human consumption. However, mercury concentration levels in the blood of goats grazing along the banks of Middle Olifants and Mogalakwena rivers were above the maximum permissible limit of 0.2 mg/litre of blood. It was concluded that meat, livers and kidneys of the goats were fit for human consumption. However, blood from these goats was not fit for human consumption.
Thesis (M. Sc. Agriculture (Animal Production)) -- University of Limpopo, 2021
Keywords: Cadmium; Chromium (Cr); Nickel (Ni); Zinc (zn); Mogalakwena; Lead (Pb); Mercury (Hg); Heavy metals -- Environmental aspects; Chromium; Cadmium -- Environmental aspects; Lead compounds; Mercury; Zinc compounds; Nickel compounds